Abnehmende Bindungsquoten in Deutschland: Ausmaß und Bedeutung eines historischen Trends - Eckhard, Jan (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2015)
This paper examines the prevalence of couple relationships in Germany using several social surveys (German Socio-Economic Panel, German Family Panel, German Family Survey, Survey of Health, Ageing and Retirement in Europe). It shows, that a differentiated perception is necessary to capture the current development: In terms of consistent ties which hold a certain degree of stability, partnering is in decline. However, short-term relationships become more common. Thus, by including also short-term affairs the share of couple relationships remains almost changeless. Moreover, the study shows sex differences as well as regional and educational distinctions. A remarkable decline of couple relationships applies especially to the male population of the eastern part of Germany.